Technology Spillovers from Foreign Direct Investment in the Indian Pharmaceutical Industry - Feinberg, Susan E.; Majumdar, Sumit K. (Journal of International Business Studies, 2001)
We examine whether knowledge spillovers from MNCs’ local R&D activities benefit domestic firms in the Indian pharmaceutical industry from 1980-1994. In a policy environment that restricted FDI and provided weak intellectual property protection, we find that the only significant R&D spillovers in the Indian pharmaceutical sector were between MNCs and each other. We explore the implications of our findings in light of India's economic and industrial policy goals and implementation.